An analysis of modification structures used in oral and written compositions of grade six pupils of Pasig Elementary School in 1970-1971 - Gatchalian, Concepcion Santos 1932- (1972)
This study focused on an analysis of modification structures used in oral and written compositions of grade six pupils of Pasig Elementary School. It sought to find out the pupils' linguistic maturity in a second language as reflected in their use of modification structures. An individual structured interview and a writing group were conducted in this study. The findings of the study showed that the pupils in the oral language group used more word modifiers than phrase modifiers, while the writing group used more phrase modifiers than word modifiers. Clause modifiers were least used by both groups.